Integrating subjectively-derived choice sets to expand offender decision-making. Issue 1 (1st January 2023) - Kijowski, Matthew C.; Wilson, Theodore
ABSTRACT: Rational choice and offender decision-making are premised upon each individual's weighing of their subjectively perceived behavioral options. However, most applications have failed to account for the heterogeneity in the options individuals perceive to have available to them within their choice set. We leveraged interdisciplinary scholarship from the fields of neuroscience and psychology to develop a strategy to capture the choice set of perceived options. Using a community sample of adults randomly assigned to one of two vignettes, we asked respondents to list the options they perceived to have available to resolve the given vignette. We then classified those options into one of four categories: pure conformist, abstain, pure criminal, or hybrid wherein an option was simultaneously criminal and prosocial. We found extensive heterogeneity in both the options and choice sets arising from each vignette. Most individuals did not note any criminal options while hybrid options appeared to a non-trivial degree in only one of the two vignettes. Our findings highlight the pitfalls associated with providing respondents with options as compared to having them subjectively construct their own options, while also pointing to how choice sets can provide a more descriptively accurate assessment of decision-making processes.